1961
DOI: 10.1002/food.19610050603
|View full text |Cite
|
Sign up to set email alerts
|

Zur Resorption von Sorbit und Mannit

Abstract: H. RUTTLOFF und H.-A. KETZ unter techn. Mitarbeit von H. WITT, I. TIETZ und I. EMMER I . Literatwubersicht Zwei ernahrungsphysiologisch bedeutsame Effekte lassen die Frage nach der Resorbierbarkeit von Zuckeralkoholeninsbesondere von Sorbitvon Interesse erscheinen, namlich einmal die erstmals von S. J. THANNHAUSER und K. H. MEYER [I] beobachtete Tolerierung groaerer Sorbitmengen durch den diabetischen Organismus, zum andern die in jungster Zeit von T. B. MORGAN und J. YUDKIN [2] beobachtete Vitamin B,-sparende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
1
1

Year Published

1963
1963
1993
1993

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
1
3
1
1
Order By: Relevance
“…The lack of SDH mRNA in this tissue could be in accordance with findings showing that sorbitol resorption in rat occurs by means of passive diffusion in jejunum and ileum (Lauwers et al, 1985), yielding sorbitol in the portal vein shortly after injection into the small intestine (Ruttloff and Ketz, 1961). At the same time, plasma sorbitol concentrations were very low (Ruttloff and Ketz, 1961), indicating substantial hepatic uptake and metabolism of sorbitol, in agreement with the large amounts of SDH mRNA in the liver (Table 1).…”
Section: Tissuesupporting
confidence: 74%
“…The lack of SDH mRNA in this tissue could be in accordance with findings showing that sorbitol resorption in rat occurs by means of passive diffusion in jejunum and ileum (Lauwers et al, 1985), yielding sorbitol in the portal vein shortly after injection into the small intestine (Ruttloff and Ketz, 1961). At the same time, plasma sorbitol concentrations were very low (Ruttloff and Ketz, 1961), indicating substantial hepatic uptake and metabolism of sorbitol, in agreement with the large amounts of SDH mRNA in the liver (Table 1).…”
Section: Tissuesupporting
confidence: 74%
“…It should be kept in mind that a comparison of GPS and GPM did not produce any real difference in energy-limited growth of rats, which proves equal utilisation of bound sorbitol and mannitol respectively. This finding is at variance with the reported, almost complete non-utilisation of free mannitol [15,17,20,27,29,41,44,49,54]; it remains to be seen whether the established slow release of mannitol from GPM (Table 1), leading to a constant, though small availability of this hexitol during intestinal passage (Table 2), could suffice to explain the different behaviour of free and glycoside-bound mannitol. Some differences between sorbitol and GPS seem to fall into the same category since free sorbitol, in contrast to GPS, does not exhibit reduced caloric utilisation in maintenance experiments 3.…”
Section: Discussioncontrasting
confidence: 70%
“…Mitchell et al (1937) observed a slight impairment in the digestibility of organic nutrients in a sucrose ration for rats, as compared with a ration containing glucose, and a slower rate of growth and of protein deposition on a fructose-containing ration. In the same species, Ruttloff and Ketz (1961) observed a decreased absorption rate for fructose as compared with glucose.…”
mentioning
confidence: 77%